Hydrogenated amorphous carbon as protective coating for a forming tool - Martinatti, J. F. [UNESP]; Santos, L. V.; Cruz, N. C. [UNESP]; Rangel, E. C. [UNESP] (Cambridge University Press, 2011)
This paper investigates the performance of hydrogenated amorphous carbon (a-C:H) films as protective coatings for a forming tool made from AISI M2 steel coated with a titanium nitride (TiN) PVD commercial layer. The samples were initially cleaned in ultrasonic baths and subsequently in a plasma ablation procedure. Films were then deposited by plasma immersion ion implantation using 91% of acetylene and 9% of argon at a total pressure of 5.5 Pa. Samples were biased with high voltage negative pulses, P (T = 3.33 ms, pulse on-time: 0.03 ms, pulse off-time: 3.30 ms and application rate: 299 Hz) with amplitudes varying from 1.000 to 4.000 V. The chemical structure and composition of the films were evaluated by infrared spectroscopy. The roughness was determined by profilometry while the surface topography and morphology were investigated by atomic force microscopy and scanning electron microscopy, respectively. The friction coefficient was determined by the ball on disk technique. A decrease in the proportion of C-H and O-H groups was observed while the concentration of dangling bonds enhanced with increasing P. Sharp structures were detected on the film surface affecting roughness in two different ways: it increased with enhancing pulse magnitude in the smoothest substrate (AISI M2) and decreased in the roughest one (AISI M2-TiN). The best tribological result was found for the sample deposited with 3.600 V of bias onto TiN-AISI M2 steel.